Disruption and Convergence : Generating New Conversations through Arts Research - Bourgault, Rébecca,; Rosamond, Catherine, (Doing Arts Thinking: Arts Practice, Research and Education ;, 2024)
Conceptualized as a tool to expand creativity, questioning, and experimentation in arts research, Disruption and Convergences: Generating New Conversations through Arts Research offers timely narratives, musings, and descriptions of experimental and scholarly practice that ignite new creative considerations for graduate students and aspiring arts research practitioners. The book features a collection of practice-based research projects for which the experiential unfolding leads to unexpected outcomes. In its openness and generativity, this mode of questioning removes the need for conclusive findings. Prominent threads that emerged from the collection encompass collaboration and interconnectedness, disputed and shared spaces, and transformation through storytelling. Contributors to the book address ways of knowing that complicate familiar categories, learning with and listening to the fragile, the provisional, and heralding unthought futurity. Disruption and Convergences offers a scholarly and artistic exchange through dialogues between contributors and invites artful and multisensorial expressions, imaginative experimentations, poetic and critical propositions that carry the voices of creators at different stages in their research careers. This form of publication is itself an international symposium of sorts, and therefore an opportunity for readers to engage in wide-ranging approaches to making, writing, and arts thinking. Contributors are: Cathy Adams, Jelena Aleksic, Carolina Bergonzoni, Rébecca Bourgault, Rachel Epp Buller, Aurora Del Rio, Christine D'Onofrio, Hannah L. Drake, Emese Hall, Damali Ibrek, Rabeya Jalil, Estée Klar, Linda E. Kourkoulis, David LeRue, Stephanie Loveless, Katri Naukkarinen, Yolanda M. Manora, Rachel Payne, Patti Pente, Nicole Rallis, Roni Raviv, Catherine M. Roach, Catherine Rosamond, Myrtle Sodhi and Alex Wexler.